Pragmatic Failure in Interpreting Some Proverbs found in SMAN 1 Lubuk Alung - Yeyep Natrio (JURNAL ARBITRER, 2018)
Phenomenon of using proverb in academic environment particularly school is usual right now. Not only using Indonesian proverb but also using English proverb, students are interested to apply them. The trend to use English as the L2 in presenting good philosophy of life is one method to help students to master and acquaintance with English. In term of English proverb, it is usually used to present condition of school environment, students, and the regulation of school which are managed systematically. Particularly, most of the English proverbs in SMAN 1 Lubuk Alung are applied to boost motivation of the students. In fact, there are some of them are misled in transferring the meaning from the real receptor language. The translation of the proverbs were dull and were not appropriate to English sense as receptor language. Learners are unaware of the pragmatic knowledge that a proverb has because they do not recognize the purpose of the communicative act that a proverb has socio-pragmatically. I conclude that the proverbs which were taken from Senior High School No. 1 Lubuk Alung, West Sumatera tends to the incorrect translation so that the students have a problem called pragmatic failure. The process of applying the English proverbs to represent the Indonesian proverbs is not suitable in the Receptor Language (RL), English. There is misleading of choosing word and also the arrangement/ structure of those words. The effort of delivering similar message in another language was failed since they did not know how to transfer knowledge about linguistic, cultural, and social information about the target language.